A Genetic Algorithm to Model Solar Radio Active Regions From 3D Magnetic Field Extrapolations - de Oliveira e Silva, Alexandre José; Selhorst, Caius Lucius; Costa, Joaquim E. R.; Simões, Paulo J. A.; Giménez de Castro, Carlos Guillermo; Wedemeyer, Sven; White, Stephen M.; Brajša, Roman; Valio, Adriana (Frontiers in Astronomy and Space Sciences, 2022)
In recent decades our understanding of solar active regions (ARs) has improved substantially due to observations made with better angular resolution and wider spectral coverage. While prior AR observations have shown that these structures were always brighter than the quiet Sun at centimeter wavelengths, recent observations at millimeter and submillimeter wavelengths have shown ARs with well defined dark umbrae. Given this new information, it is now necessary to update our understanding and models of the solar atmosphere in active regions. In this work, we present a data-constrained model of the AR solar atmosphere, in which we use brightness temperature measurements of NOAA 12470 at three radio frequencies: 17, 100 and 230~GHz. The observations at 17~GHz were made by the Nobeyama Radioheliograph (NoRH), while the observations at 100 and 230~GHz were obtained by the Atacama Large Millimeter/submillimeter Array (ALMA). Based on our model, which assumes that the radio emission originates from thermal free-free and gyroresonance processes, we calculate radio brightness temperature maps that can be compared with the observations. The magnetic field at distinct atmospheric heights was determined in our modelling process by force-free field extrapolation using photospheric magnetograms taken by the Helioseismic and Magnetic Imager (HMI) on board the Solar Dynamics Observatory (SDO). In order to determine the best plasma temperature and density height profiles necessary to match the observations, the model uses a genetic algorithm that modifies a standard quiet Sun atmospheric model. Our results show that the height of the transition region (TR) of the modelled atmosphere varies with the type of region being modelled: for umbrae the TR is located at $1080±20$~km above the solar surface; for penumbrae, the TR is located at $1800±50$~km; and for bright regions outside sunspots, the TR is located at $2000±100$~km. With these results, we find good agreement with the observed AR brightness temperature maps. Our modelled AR can be used to estimate the emission at frequencies without observational coverage.